Спектроскопія триплетных екситонів у органічних сполуках: кристалічний і склоподібний бензофенон - Melnyk, V.I.; Klishevich, G.V.; Curmei, M.D. (Publishing house "Academperiodika", 2026)
A brief overview of the main results obtained on the spectral-luminescence properties of triplet excitons in crystalline and glassy benzophenone is given. The studies were mainly performed at the Institute of Physics of the National Academy of Sciences of Ukraine. Brief information on the achievements in the physics of triplet excitons in organic semiconductors is also presented. The peculiarities of phosphorescence and the structure of the glassy benzophenone phase are discussed. The conditions for the existence of excitonic phosphorescence in molecular crystals are considered. The achievements of various authors in the molecular spectroscopy of triplet state have been analyzed. It is shown that among molecular crystals, benzophenone is one of the most convenient objects for studying phosphorescence and spectral properties of the triplet state of organic compounds.